Operational policy needs for organic agriculture expansion in the Philippines focus on vegetable - Rola, Agnes C.; Pantoja, Blanquita R.; Chupungco, Agnes R.; Nguyen, Miriam R.; Reyes, Jaine C.; Madlangbayan, Guinevere T.; Umali, Macrina G.; Guiaya, Susan S.; Martinez, Eldy Z.; Badayos, Gerdino G. (2015)
In 2010, the Philippines passed a law (Republic Act No. 10068) to support the expansion of organic agriculture (OA) in the country, with a goal of 5 percent of total production area being devoted to this technology. Available data show that in 2012, only about 0.7 percent of the agricultural land area in the country was devoted to OA production. While several other administrative orders supported the law, there seems to be a need to understand the processes to operationalize the said law.
This paper analyzed the production, marketing, and consumption issues surrounding the organic vegetable industry to come up with operational policies to support the implementation of the law. The data came from a survey of 300 vegetable farmers and 180 consumers and non-consumers of organic vegetables supported by key information from government officials, farmers' associations, and traders. Results showed that the most critical constraint to OA production was the high cost of certification, lack of farmers' training on the technology, and access to organic inputs. Alternative certification processes, capacity building for both farmers and program implementers, and more IEC campaigns on the benefits of OA products are recommended.
Keywords: Organic farming; Vegetables